DIFFERENCES OF BRAIN GYM AND GYMNASTICS WITHOUT MUSIC AGAINST DEPRESSION IN THE ELDERLY - Zharifah Al Maani; Angga Sugiarto; Hermani Triredjeki; Pramono Giri Kuswoyo (Poltekkes Kemenkes Semarang, 2019)
Background: Indonesia's elderly population is increasing with increasing life expectancy. Changes in mental health that usually becomes a problem in the elderly is depression. Depression in the elderly need to be addressed, one with creative therapy. Creative types of therapy that can influence the elderly depression is like Brain Gym and elderly gymnastics. These activities can be carried out in the elderly in the community with ease because it is their neighborhood health center and also does not require music.Purpose: This study was conducted to determine differences in the effect of brain gym and gymnastics elderly to depression in elderly Posyandu Elderly Patent Canyons, Rejowinangun North, Central Magelang, Magelang CityMethod: The approach in this study is quantitative research design with two non-equivalent group pretest posttest design. The sampling technique used is saturated samples involving all the elderly who experience depression as a sample with 56 elderly measured by GDS 15-Items. The intervention is done 2 times a week for 1 month with a time of 30 minutes.Results: The results showed that there were no differences influence of Brain Gym and exercise the elderly to depression in the elderly due to results obtained Mann Whitney test p value 0.051 (p 0.05).Conclusion: No difference elderly Brain Gym and exercise for depression in the elderly, but these activities can be applied to the activity of the elderly in reducing and preventing depression in the elderly due to the activity can lower GDS scores 15-Items.